Um método de busca usando algoritmo genético para programação reativa da produção de sistemas de manufatura com recursos compartilhados - Deriz, Ana Claudia (Universidade Federal de São Carlos, 2007)
Search strategies have been used to solve the problem of scheduling of Manufacturing Systems with Shared Resources. However, depending on the size and complexity of the manufacturing system, the response time of the search becomes critical. Reseaches aim to use of Genetic Algorithms as a search method to solve the scheduling problem. This work proposes a modeling of Genetic Algorithm to solve this problem having as performance criteria the minimum makespan of the scheduling and obtaining a low response time of the search.
A search method using genetic algorithm for reactive scheduling of sharing resources manufacturing systems
Keywords: Ciência da computação; Programação da produção; Sistemas de manufatura; Compartilhamento de recursos; Algoritmos genéticos; Scheduling; Manufacturing systems; Shared resources; Genetic algorithms; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO